PENGEMBANGAN KOMPETENSI KEPRIBADIANGURU PENDIDIKAN AGAMA ISLAM DALAM KEGIATAN MENGAJAR SISWA DI MTs MAYANG KECAMATAN BOSAR MALIGAS KABUPATEN SIMALUNGUN - Nurdiani, Rapika Dewi Damanik, Muhammad Firman Maulana (Fakultas Agama Islam, 2022)
Competence is a set of knowledge, skills and behaviors that must be possessed, lived and mastered by the teacher and has become a part of him to carry out his professional duties. Stable, mature, wise, and wise, evaluate their own performance, and develop themselves in a sustainable manner. The teacher is a very important profession in schools, so to become a teacher one must have the ability, knowledge and good personality competencies. Especially Islamic religious education teachers. In addition to teaching, Islamic religious teachers are required to be able to teach or apply moral values to their students. The research method used in this study is a qualitative research method, the type of field research. The location of this research is at MTs Mayang, Bosar Maligas District, Simalungun Regency. And the research subjects in this study were Islamic religious education teachers, other subject teachers, and students. The data collection techniques used are observation, interviews, and documentation. The observations made by the author are direct or disguised observations. And the interviews conducted by the researchers are direct interviews. other subject teachers. The results showed that the personality competence of Islamic religious education teachers at MTs Mayang, Bosar Maligas District, Simalungun Regency, both in their daily lives and their role as a teacher. This Islamic religious education teacher at MTs Mayang fulfills personality competencies, namely having an honest attitude, noble character, wisdom, maturity and establishing good communication between fellow teachers and students. better in the future